PENINGKATAN KUALITAS PRODUK TRADISIONAL PROL TAPE DENGAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Ida Bagus Suryaningrat; Wimbi Rendra (Faculty of Agricultural Technology, University of Jember, 2014)
Prol Tape is one of the local traditional food products (cake) from Jember, made from fermented cassava. Quality improvement problems were still faced by producers of prol tape. This was due to limited information of consumers’ satisfaction factors of this product. Therefore the evaluation of consumers’ respon was strongly needed to know consumers’ needs in this product. Quality Function Deployment (QFD) was used in this research to reach factors or product attributes related to consumers’ needs of prol tape product. The result of this research found that there were 4 attributes of consumers needs consisted of taste, colour, aroma and texture. There were also five technical responses from producers (production acctivities) which have close relationship to product quality. Compared to other brands, it was found that consumers prefer to select Wika than other brands (Sumber Madu, Primadona and Purnama Jati). From QFD analysis, Wika could reach the target compare to others. It means that Wika has better condition to answer consumers’ needs using tecchnical response. Some of recommended strategies are also explained briefly in this research paper.Keywords: quality, traditional product, QFD